2020
DOI: 10.3390/ijms21144823
|View full text |Cite
|
Sign up to set email alerts
|

Distal-Less Homeobox 5 Is a Therapeutic Target for Attenuating Hypertrophy and Apoptosis of Mesenchymal Progenitor Cells

Abstract: Chondrocyte hypertrophy is a hallmark of osteoarthritis (OA) pathology. In the present study, we elucidated the mechanism underlying the relationship between the hypertrophy/apoptotic phenotype and OA pathogenesis in bone marrow-derived mesenchymal stem cells (BM-MSCs) via gene targeting of distal-less homeobox 5 (DLX5). Our primary objectives were (1) to determine whether DLX5 is a predictive biomarker of cellular hypertrophy in human osteoarthritic tissues; (2) To determine whether modulating DLX5 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Cell hypertrophy is a hallmark of OA. Cartilage samples derived from patients presenting different OA statuses demonstrated a positive correlation between the levels of DLX5 expression and the severity of osteoarthritis, reinforcing the notion that DLX5 is a regulator of cellular hypertrophy, and that its inhibition could improve cell-mediated cartilage tissue repair [ 89 ]. Indeed, DLX5 expression increases with chondrocyte differentiation [ 90 ] and in OA; cultured chondrocytes from OA patients express higher levels of DLX5 and COL10 , compared with non-arthritic chondrocytes.…”
Section: DLX Genes In Cartilage Development and Maintenancementioning
confidence: 77%
See 1 more Smart Citation
“…Cell hypertrophy is a hallmark of OA. Cartilage samples derived from patients presenting different OA statuses demonstrated a positive correlation between the levels of DLX5 expression and the severity of osteoarthritis, reinforcing the notion that DLX5 is a regulator of cellular hypertrophy, and that its inhibition could improve cell-mediated cartilage tissue repair [ 89 ]. Indeed, DLX5 expression increases with chondrocyte differentiation [ 90 ] and in OA; cultured chondrocytes from OA patients express higher levels of DLX5 and COL10 , compared with non-arthritic chondrocytes.…”
Section: DLX Genes In Cartilage Development and Maintenancementioning
confidence: 77%
“…Indeed, DLX5 expression increases with chondrocyte differentiation [ 90 ] and in OA; cultured chondrocytes from OA patients express higher levels of DLX5 and COL10 , compared with non-arthritic chondrocytes. DLX5 inhibition in BM-MSCs was found to reduce cellular hypertrophy without inhibiting chondrogenic potential, while overexpression of DLX5 was associated with increased expression of cellular hypertrophy markers [ 89 ]. Articular cartilage calcification indicates cartilage damage.…”
Section: DLX Genes In Cartilage Development and Maintenancementioning
confidence: 99%
“…It has been reported that Dlx5 is upregulated in osteoarthritis cartilage [ 15 ]. To investigate the role of Dlx5 in osteoarthritis, knee osteoarthritis was induced by intraarticular injection of papain along with cysteine in rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, overexpression of Dlx5 accelerates chondrocyte hypertrophy [ 14 ]. Moreover, it has been reported that Dlx5 is upregulated in osteoarthritis cartilage [ 15 ]. However, whether Dlx5 plays a role in osteoarthritis progression has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal progenitor cells derived from healthy articular cartilage, herein referred as CPCs, are a small subset of cells that are highly proliferative, chondrogenic, and migratory ( Dowthwaite et al, 2004 ; Seol et al, 2014 ; Jayasuriya and Chen, 2015 ; Jayasuriya et al, 2016 ), making them a potentially useful resource for biologic cell therapy and cartilaginous tissue engineering applications ( McCarthy et al, 2012 ; Seol et al, 2014 ; Bilgen et al, 2018 ; Park et al, 2020 ). Further, they are resistant to cellular hypertrophy and terminal differentiation ( McCarthy et al, 2012 ; Twomey-Kozak et al, 2020 ), unlike mesenchymal progenitor/stem cells from bone marrow and osteoarthritic (diseased) cartilage tissue ( Jayasuriya et al, 2018 ; Hu et al, 2019 ; Liu et al, 2020 ). We have recently demonstrated the efficacy of using stable CPC lines, either as such or in a collagen coated hydroxypropyl cellulose scaffold, to stimulate meniscus injury repair in rat and human ex-vivo organ culture model systems, respectively ( Jayasuriya et al, 2019 ; Newberry et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%